Structural Genomic Variation as Risk Factor for Idiopathic Recurrent Miscarriage. Issue 8 (24th June 2014) - Nagirnaja, Liina; Palta, Priit; Kasak, Laura; Rull, Kristiina; Christiansen, Ole B.; Nielsen, Henriette S.; Steffensen, Rudi; Esko, Tõnu; Remm, Maido; Laan, Maris
<x xml:space="preserve">Abstract</x> This study highlights the impact of DNA copy number variants (CNVs) as the risk factor of recurrent miscarriages. Genome‐wide profile of CNVs in recurrent miscarriage cases specifically altered pathways of immune tolerance known to be essential at the fetomaternal interface of the placenta. A novel multi‐copy duplication at 5p13.3 was identified conferring maternal risk to recurrent miscarriage disease and disrupting PDZD2 and GOLPH3 genes expressed in placenta and associated with early pregnancy success for the first time. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>